The Importance of Second-Hand Knowledge in the Revised Uppsala Model: Can European Textiles Producers Export to China? - Susana Costa e Silva (2012)
The authors studied how knowledge derived from firms' relationships-the so-called second-hand knowledge-is likely to influence their internationalization process. In this article, they examine how a European producer of textiles is able to sell worldwide, including to China, a highly competitive player in this industry. This article discusses models of firms' networks and the extent to which such networks generate important knowledge that can explain internationalization behavior-how it is able to influence the selection of foreign markets and the entry mode used. The authors use the revised version of the Uppsala model of internationalization, which emphasizes the roles of trust-building, knowledge, and creation of opportunities within relationships.